Extraartikulární subtalární artrodéza podle Grice u pacientů s dětskou mozkovou obrnou: zhodnocení střednědobých výsledků - Němejcová, E; Schejbalová, A; Trč, T; Havlas, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY The aim of the study was to evaluate, on the basis of radiographic findings and AOFAS scores, the results of the Grice extra-articular subtalar arthrodesis for treatment of planovalgus foot deformity in cerebral palsy patients. MATERIAL AND METHODS A total of 38 patients (50 feet) with cerebral palsy indicated to the Grice procedure for planovalgus foot deformity between 2006 and 2010 were assessed. The group comprised 18 girls and 20 boys, of whom 10 had spastic quadriparesis (four undergoing bilateral surgery), three had triparesis, four had hemiparesis and 21 had diparesis (treated on both sides in eight). The average age at surgery was 12 years (range, 7 years and 2 months to 17 years and 8 months). All patients were evaluated based on the AOFAS scoring system and radiographic findings before and after surgery. RESULTS The average follow-up was 4.5 years. The average AOFAS score increased from 54.9 points pre-operatively to 76.6 points post-operatively. The pre- and post-operative average values for the talocalcaneal angle were 49.8° and 25°, respectively; for the calcaneal inclination angle they were 8.6° and 13.4°, respectively. DISCUSSION The Grice procedure has long been considered a primary surgical treatment for planovalgus foot deformity in patients with cerebral palsy. Recently, calcaneal osteotomy has been used more frequently, but with no evidence of provably better results. CONSLUSIONS The mid-term results of the Grice extra-articular arthrodesis in our group of cerebral palsy children were very good in terms of both radiographic and AOFAS score evaluation; the latter includes objective assessment as well as the patient's subjective evaluation. KEY WORDS: Grice procedure, extra-articular subtalar arthrodesis, cerebral palsy, planovalgus foot deformity.
Keywords: Calcaneus; subtalární kloub; Female; dítě; výsledek terapie; ženské pohlaví; artrodéza; Adolescent; lidé; mozková obrna; Cerebral Palsy; Treatment Outcome; Subtalar Joint; patní kost; Male; Arthrodesis; Child; mužské pohlaví; mladiství; Humans